Temperature Distribution on the Surface of LED Lamps; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Lebedev S. M. Sergey Mikhailovich (Materials and Technologies in Optoelectronics Production, 2016)
Title screen